On trajectory tracking control of simple port-Hamiltonian systems based on passivity based sliding mode control. Issue 19 (2021) - Sakata, N.; Fujimoto, K.; Maruta, I.
Abstract: In this work, the passivity-based sliding mode control technique is applied to trajectory tracking control problems. This method unifies two methods, sliding mode control and passivity-based control, and has the advantages of both control methods. This paper proposes a pair of a pre-coordinate transformation and a state feedback so that we obtain a desired error port-Hamiltonian system that describes the dynamics of the tracking error. This approach enables us to obtain appropriate design parameters satisfying a kind of matching condition to realize sliding mode control with a Lyapunov function. The effectiveness of the proposed method is demonstrated by a numerical simulation.